Penerapan Metode Kangguru Menggunakan Jarik terhadap Berat Badan dan Suhu pada Bayi Berat Badan Lahir Rendah (BBLR) di RSUD Pandan Arang Boyolali - Khasanah, Umi; Husain, Fida' (Barongko: Jurnal Ilmu Kesehatan, 2023)
Data from WHO 2020 Low Birth Wheight (LBW) is estimated at 21% of all births in the world with a limit of 4,5-49% and is more common in developing countries, the incidence of LBW in Asia is 42,7%. The WHO recommends the kangaroo method for babies whose weight is <2000 grams. The purpose of this study was to determine the development of body temperature and body weight before and after the application of the kangaroo methode using jarik to two respondents. This research is a case study research using descriptive methode, nemely by observing and interviewing two respondents who experienced LBW before and after applying to two respondents there was an increase in body temperature and weight on the first day By.Ny.A 35,9◦C to 36,6◦C and 1600 grams to 1715 grams while By.Ny.K 35,6◦C becomes 36,6◦C and 1613 grams becomes 1724 grams. The conclusion of the thuis study is that after applying the kangaroo methode using jarik to By.Ny.A and By.Ny.K there is an increase in body temperature and body weight in the LBW category. This shows that the kangaroo method using jarik can increas body temperature and body weight in both respondents.